1996
DOI: 10.3109/00016349609033276
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus radical surgery for tubal pregnancy

Abstract: In studies on fertility after radical or conservative surgical treatment for tubal pregnancy no significant difference in intrauterine pregnancy rates or repeat ectopic pregnancy rates were found. Prospective selected treatment series demonstrated higher intrauterine pregnancy rates than retrospective studies. The repeat ectopic pregnancy rate was not raised in prospective series. No prospective randomised trial was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 29 publications
1
37
0
3
Order By: Relevance
“…No significant difference regarding pregnancy rate between operative laparoscopy and laparotomy could be observed. The results of the present study regarding repeat EP are in agreement with Clausen [11], who also found no difference in the occurrence of repeat EP after conservative or radical surgical treatment. In Clausen's material, 10% had a repeat EP after conservative treatment and 15% after radical treatment.…”
Section: Discussionsupporting
confidence: 92%
“…No significant difference regarding pregnancy rate between operative laparoscopy and laparotomy could be observed. The results of the present study regarding repeat EP are in agreement with Clausen [11], who also found no difference in the occurrence of repeat EP after conservative or radical surgical treatment. In Clausen's material, 10% had a repeat EP after conservative treatment and 15% after radical treatment.…”
Section: Discussionsupporting
confidence: 92%
“…1 This procedure preserves the fallopian tube, thereby maintaining reproductive capacity, but, in comparison with salpingectomy, carries an increased risk of persistent trophoblast and, possibly, of repeat ectopic pregnancy in the operated tube. 2,3 Another approach that preserves tubal integrity is medical treatment, in particular the systemic administration of methotrexate. Since laparoscopy is no longer essential for diagnosis in patients with suspected ectopic pregnancy, methotrexate offers the option of completely non-surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a prospective study of 88 patients by Ory et al indicated that the surgical method had no effect on subsequent fertility in women with an intact contra-lateral tube [21]. Several other studies reported that the status of the contra-lateral tube, the presence of adhesions, and the presence of other risk factors, such as endometriosis, have a more significant impact on future fertility than does the choice of surgical procedure [ 61 ] .…”
Section: Discussionmentioning
confidence: 99%